Dinâmica dos incêndios florestais no estado do Acre - Silva, Sonaira Souza da (Instituto Nacional de Pesquisas da Amazônia – INPA, 2017)
Over the last 40 years, forest fires in Amazonia have occurred at intervals of 4 to 5 years, causing economic, environmental and social damage. To understand the spatial and temporal dynamics of forest fires in Brazil’s state of Acre over a period of 33 years (1984 to 2016), we used images from Landsat 5, 7 and 8, applying the burn scar index (BSI) derived from the fractions of photosynthetic material, non-photosynthetic material and soil generated by CLASlite© software. Based on this mapping, we used the weights of evidence method in Dinamica-EGO software to analyze the factors resulting from human action and from natural features of the landscape that have the strongest influence on the occurrence of forest fires. To understand the changes in the forest, we selected four areas based on mapping the 2005 and 2010 fires and their areas of overlap. In this forest inventory we measured the diameter at breast height of all living and dead individuals larger than 10 cm in diameter in three 100 m × 50 m plots and all bamboo culms independent of diameter in 5 m × 5 m sub-plots. Information was collected on the total height of trees, whether the trees were broken or pressured by bamboo and whether termites were present. The total area of forest impacted by the fire in the period of 33 years in the entire State of Acre was 5,251 km 2 . However, of this total there were forests that were affected by fire only once (3,883 km 2 ), twice (598 km 2 ) and three times (57 km 2 ). In 2005, the municipalities (counties) of Acrelândia, Plácido de Castro and Senador Guiomard had more than 50% of their remaining forest impacted by fire. The main factors favoring fire occurrence were fragmentation and the proximity of cattle pastures and roads. Forest types most susceptible to fire were open forest with bamboo, open forest with palms and alluvial forest. Degradation caused by fire caused a strong impact in the reduction of density trees, species richness and decreases in dry above-ground biomass. An additional effect of the impact of the fire was an expansion of bamboo to densities 7 to 9 times that in unburned forest. The expansion of the bamboo had a linear relationship with decrease in the number of trees, in addition to increasing the number of trees damaged and broken, affecting up to 24% of all trees. For the open forests of southwestern Amazonia it is important to consider the contribution of bamboo (Guadua) in estimates of the total above-ground biomass of the forest. Bamboo increases the total biomass by 3 Mg ha -1 in intact forest, 26 Mg ha -1 in forest burned in 2005, 23 Mg ha -1 in forest burned in 2010 and 26 Mg ha -1 in forest burned in both 2005 and 2010, raising the biomass by percentages ranging from 1% to 38% with respect to the tree component. Up to 2016, the reduction of forest biomass caused a committed emission of 38 Tg of CO 2 for the state of Acre in an area of 3800 km 2 of remaining forest that had been affected by fire. This Xcommitted emission reduces by 17% the net climatic benefit of Acre’s goal for reducing the state’s greenhouse-gas emissions by 2020. This study made it possible to understand the scale of forest fires and their impacts in the forests of the state of Acre in drought years, which points to a future full of challenges for reducing the process of forest degradation.
Keywords: Secas extremas; Gases de efeito estufa; Expansão do bambu